2021
DOI: 10.3389/978-2-88971-048-5
|View full text |Cite
|
Sign up to set email alerts
|

Plastics in the Environment: Understanding Impacts and Identifying Solutions

Abstract: Frontiers is more than just an open-access publisher of scholarly articles: it is a pioneering approach to the world of academia, radically improving the way scholarly research is managed. The grand vision of Frontiers is a world where all people have an equal opportunity to seek, share and generate knowledge. Frontiers provides immediate and permanent online open access to all its publications, but this alone is not enough to realize our grand goals. Frontiers Journal SeriesThe Frontiers Journal Series is a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 320 publications
0
1
0
Order By: Relevance
“…Babayemi et al (2018) reported that less than 12% of plastic wastes in Nigeria are being recycled; the rest end up in landfills and dump sites and may also be disposed by open burning, which causes air pollution. Unless significant breakthrough in the management of plastic design or waste is achieved, plastic emissions are projected to increase in the future; and this could impact ecological processes or the global carbon cycle (Filella et al, 2021). Hence, creating proper and improved plastic wastes management solutions has become a common global interest (Kawai et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Babayemi et al (2018) reported that less than 12% of plastic wastes in Nigeria are being recycled; the rest end up in landfills and dump sites and may also be disposed by open burning, which causes air pollution. Unless significant breakthrough in the management of plastic design or waste is achieved, plastic emissions are projected to increase in the future; and this could impact ecological processes or the global carbon cycle (Filella et al, 2021). Hence, creating proper and improved plastic wastes management solutions has become a common global interest (Kawai et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Our first collection of Frontiers articles highlighted the broad diversity of environmental problems caused by the mismanagement of plastics in different settings, and the many challenges that scientists, managers, regulators and stakeholders face in addressing these problems (Filella et al, 2021). This, second series essentially deals with plastics in soils and the degradation of plastic (and in particular, expanded polystyrene).…”
mentioning
confidence: 99%